Establishment of regenerative callus, cell suspension system, and molecular characterization of Taxus wallichiana Zucc. for the in vitro production of Taxol - Dhurva Prasad Gauchan, Sudina Bhuju, Janardan Lamichhane, Rajani Shakya, María Rosario García-Gil (Journal of Applied Pharmaceutical Science, 2021)
Taxus wallichiana, an endangered Taxus species native to Nepal, is a source of Taxol (paclitaxel), an anticancer drug, which if produced via plant cell culture in vitro not only reduces the pressure on natural habitat but also allows continuous production throughout the seasons. Gamborg’s B5 medium was the culture medium to develop callus and suspension culture. Quantification of Taxol was carried out via high performance liquid chromatography (HPLC) using C18 column, water-acetonitrile mobile phase, and 1 ml/minute flowrate at 227 nm wavelength. Genetic variation among population was determined using the POPGEN32, version 1.31. Best callus response was in medium with 1 mg/l 2,4-D for both stem and needle explants. For cell suspension culture, callus from needle explants showed better response compared to stem. Fructose and sucrose proved to be the best carbon sources. Cell count increased as carbon concentration increased. 2,4-D at low concentration (5 mg/l) showed higher cell growth rate. Inoculum volume was directly proportional to cell count. Extra addition of macronutrients had inhibitory effect on cell count, but the effect was reversed for MgSO4. Using HPLC, for bark, the highest Taxol yield was 0.057 mg/g distilled water (DW), while for needle was 0.056 mg/g DW. For suspension cultured HPLC samples, Taxol yield ranged at 0.004%. Size range of amplified Deoxyribonucleic acids was between 200 and 2,000 bp. Thus, this investigation generated a concrete data for Taxus population of Nepal providing efficient protocols for establishment of callus and cell suspension culture with the aim of producing Taxol in in vitro conditions.
Keywords: Taxus wallichiana, Taxol, cell suspension culture, HPLC, RAPD-PCR.